Myocardial deformation in children post cardiac surgery, a cross-sectional prospective study - Mohammad Ahmad Hassan; Ali Al-Akhfash; Yasser Bhat; Abdullah Alqwaiee; Mohammed Abdulrashed; Saad Saleh Almarshud; Abdulrahman Almesned (The Egyptian Heart Journal)
Abstract Background Myocardial deformation by speckle tracking echocardiography provides valuable information on the left ventricular function. The study aims to assess myocardial deformation in terms of left ventricular strain as an indicator of myocardial function in children after cardiac surgery at outpatient follow-up visits. Methods The study design was a prospective observational cross-sectional study that included pediatric patients after biventricular cardiac surgery during the postoperative follow-up visits in the outpatient department. In addition to conventional echocardiographic examination, two-dimensional speckle tracking echocardiography was done to evaluate myocardial deformation in terms of left ventricular strain. Echocardiographic measurements were done offline and were compared to published reference normal values for age. Study subjects were divided according to age at follow-up into four groups (1 month–1 year, 1–2 years, 2–5 years, and 5–11 years). Results Over ten months, 100 patients (64 males and 36 females) were included in the study. The median age was 30.8 months (IQR 12.8–65.3 months), the median weight was 11.7 kg (IQR 8–17 kg) and the median duration after surgery was 7.3 months (IQR 3.2–30.8 months). Longitudinal strain values were significantly (p < 0.001) lower than reference values for different age groups. Global circumferential strain showed no significant difference from the reference values. The duration after surgery had a statistically significant effect on longitudinal strain values, with improvement of the strain values with increasing intervals after surgery. Conclusion Using myocardial deformation method to evaluate cardiac function may detect underlying cardiac function abnormalities even with normal traditional functional parameters, which could have implications for patient management and follow-up.